Faktor Nasabah Memilih BMT Mandiri Sejahtera Gresik - Syukron Makmun; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research is set to determine the factors that influence the customer in choosing BMT Mandiri Sejahtera Gresik which has a customer base of more than twenty thousand. This study uses a quantitative method with exploratory factor analysis. Characteristics of the population in this study is the customer BMT Mandiri Sejahtera. The number of samples at the time of the interview written test prelemenery test as 9 respondents, and to main test as many as 85 respondents. Sampling technique used was purposive sampling where the sample is taken from the customer BMT Mandiri Sejahtera Karangcangkring Central Office. Based on the results of the study indicate that there are six factors that affect the customer's decision choosing BMT Mandiri Sejahtera. Six such factors as a result of reduction of the processing of factor analysis. These six factors are named by a factor of revenue sharing, religiosity factors, factors of marketing strategies, factors saving gift, factor customer service, and the administrative cost factor.